Static Krivoglaz—Debye—Waller Factor for Spherical New-Phase Particles - Skakunova, O.S. (Металлофизика и новейшие технологии, 2015)
The explicit analytical expression for the static Krivoglaz—Debye—Waller factor is derived in the case of spherical amorphous clusters or new-phase particles. The simple approximate formulas are obtained in limiting cases of both small static distortions and large ones around the defects.